Prevalence and Antimicrobial Resistance of Diarrheagenic Escherichia coli and Shigella Species Associated with Acute Diarrhea in Tehran, Iran - Fereshteh Jafari; Mohammad Hamidian; Maryam Rezadehbashi; Michael Doyle; Siavosh Salmanzadeh-ahrabi; Faramarz Derakhshan; Mohammad Reza Zali (Canadian Journal of Infectious Diseases and Medical Microbiology)
A study was performed to determine the prevalence and antimicrobial resistance of Shigella species and diarrheagenic Escherichia coli isolates cultured from patients with acute diarrhea in Tehran, Iran. Between May 2003 and May 2005, 1120 diarrheal specimens were collected and assayed for bacterial enteropathogens by conventional and molecular methods. Etiological agents were isolated from 564 (50.3%) specimens, and included 305 (54%) E coli, 157 (27.8%) Shigella species, and 102 (18%) from other genera of bacteria. The predominant E coli was Shiga toxin-producing E coli (105 isolates [34.5%]) and the predominant Shigella serotype was Shigella sonnei (88 isolates [56.1%]). A high rate of antibiotic resistance was observed among E coli, with 40 of 53 (75.5%) Shiga toxin-producing E coli isolates resistant to amoxicillin and tetra-cycline, and eight (5.2%) E coli isolates resistant to more than six antibiotics. Most Shigella isolates were resistant to tetracycline (95%) and trimethoprim-sulfamethoxazole (91.7%), with greatest antibiotic resistance observed among S sonnei (53 of 88 [60.2%] isolates). Antibiotic resistance is widespread in diarrheagenic E coli and Shigella in children with acute diarrhea in Tehran, Iran; hence, updated strategies for appropriate use of antimicrobial agents in Iran are needed.